Short-time work in Europe: Rescue in the current COVID-19 crisis? - Regina Konle-Seidl (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2020)
More countries than ever are using short-time work as a labour market policy instrument to secure employment and limit the social costs of the current Corona crisis. Despite considerable differences in the institutional design and logic of short-time work schemes, the rapid deployment and high take-up of short-time work benefits is a high priority in all European countries. Highlighting the economic rationality of short-time work the report classifies European short-time work programmes into different clusters. The paper describes significant changes in the programme design since March 2020 and discusses possible effects against the background of former empirical findings. – – In der aktuellen Corona-Krise wird in mehr Ländern als jemals zuvor Kurzarbeit als arbeitsmarktpolitisches Instrument eingesetzt, um Beschäftigung zu sichern und die sozialen Kosten der Krise zu begrenzen. Trotz erheblicher Unterschiede in der institutionellen Ausgestaltung und Logik von Kurzarbeitsregelungen hat der rasche Einsatz und eine hohe Inanspruchnahme von Kurzarbeitergeld eine hohe Priorität in allen europäischen Ländern. Der Beitrag beschreibt die ökonomische Rationalität von Kurzarbeit und ordnet die europäischen Kurzarbeitsprogramme in verschiedene Cluster ein. Er beschreibt wesentliche Veränderungen in der Ausgestaltung seit März 2020 und diskutiert mögliche Wirkungen vor dem Hintergrund empirischer Erkenntnisse aus früheren Krisenzeiten.
Keywords: 330; Global health crisis; labour market policy measures; short-time work; unemployment; social security